Management of severe dysplastic nevus (high-grade dysplasia): Italian recommendations for good clinical practice - Massone, Cesare; Argenziano, Giuseppe; Cota, Carlo; Ferrara, Gerardo; Massi, Daniela; Cusano, Francesco; Fino, Maria; Mitrova, Zuzana; Saulle, Rosella (Dermatology Reports, 2026)
“Dysplastic nevus” (DN) is a histopathological term used to describe nevi with cytological atypia and architectural disorder. With the 2018 World Health Organization (WHO) classification, the grading system for atypia/dysplasia was simplified into two categories: low-grade dysplasia and high-grade dysplasia (severely atypical dysplastic nevus [SDN]); this classification is currently in use, and its criteria are applied by pathologists for the diagnosis of DN. Actually, there are currently no definitive guidelines for managing patients with DN. This lack of clear direction has historically led many specialists, both dermatologists and others, to perform or request a further widening of a lesion diagnosed as an SDN, even when it has already been completely excised, effectively treating it as a melanoma in situ (MIS). This tendency leads to a significant increase in the number of surgical procedures, consequently lengthening dermatological surgery waiting lists. Therefore, reducing the number of inappropriate widenings would have a strong impact on shortening these waiting lists, in addition to the physical and psychological impact a second procedure has on the individual patient. Moreover, the management of histologically severe DN has alternatives to widening because dermatologists can opt for observation (digital monitoring). The Italian National Center for Clinical Governance and Healthcare Excellence (CNCG) of the Istituto Superiore di Sanità (ISS) identified the scientific Italian Association of Hospital Dermatologists (ADOI) as the lead organization for the recommendations for good clinical practice on the management of SDN. Further, twelve scientific societies were involved. A systematic literature search was conducted on the following databases: Cochrane Library, MEDLINE, and Embase up to November 27, 2024. Only two retrospective, monocentric observational studies were considered eligible for the study because they had outcome data for both re-excised and observed patients with the specific histological diagnosis of severe atypia and negative margins, and one relevant systematic review. A GRADE-based assessment was conducted using a narrative summary of findings. The quality of evidence was rated as very low, based on the results from the two non-randomized studies: 0 events among 213 observed patients and 0 events among 101 re-excised patients (total n=314). The available data suggest that observation alone may be a safe alternative to re-excision. The omission of re-excision for DN with negative margins does not appear to increase the subsequent risk of melanoma. The Expert Panel unanimously judged the desirable effect of re-excision in reducing melanoma occurrence to be negligible when compared to observation alone. After collegial discussion, the Expert Panel’s judgment on the question, “In patients with a histological diagnosis of a completely excised high-grade DN (with negative margins), is re-excision of the surgical site more effective than clinical follow-up alone in reducing the risk of a recurrent nevus or melanoma?” was “probably not”. The panel suggests that, in the absence of clear scientific evidence, further enlargement/radicalization of a high-grade DN, when it has already been completely removed by elliptical excision, does not appear to be necessary. Furthermore, since it is well known that the differential diagnosis between high-grade DN and early melanoma is complex and difficult even for experienced pathologists, in controversial cases, the Expert Panel suggests, for a definitive decision, referring to a clinicopathological correlation to be assessed on a case-by-case basis.